The Analysis of Total Dissolved Iron from Mud Sedimentation Ponds Wastewater in PT Bukit Asam (Persero) Tbk Tanjung Enim Using Individual Control Diagram - Getari Kasmiarti; Bambang Yudono (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
The tests have been carried out on the iron content of wastewater in the inlet and outlet of the mud sedimentation ponds PT Bukit Asam (Persero) Tbk Tanjung Enim, South Sumatra Province. The iron concentration in mining waste water that does not comply with government standards of 7.0000 mg / L can pollute the environment. The measurement of iron concentration was carried out by Atomic Absorption Spectrophotometer (AAS) method in accordance with SNI 06-6989.4: 2004. Analysis of iron concentration using calibration curve methods and individual control diagrams. The results of data analysis showed that the iron content of the inlet and outlet MSP (Mud Sedimentation Ponds) wastewater was still under the standard set with an average value of 1.4488 mg/L inlet and outlet 0.4061 mg/L. Based on the results of the study the concentration of iron meets the established quality standards.